An engineered Yarrowia lipolytica with rapid growth and efficient lipid utilization - Tianyu Dong; Yujie Shu; Ying Wang; Mingdong Yao; Wenhai Xiao (Synthetic and Systems Biotechnology, 2025)
Yarrowia lipolytica, a safe yeast, efficiently metabolizes lipids for the production of food additives and agricultural products. Boosting its growth and lipid utilization capabilities is crucial to enhancing the overall efficiency Y. lipolytica. Herein, an integrated strategy was implemented to enhance lipid uptake, accumulation and metabolism and systematically promote the growth and lipid utilization of the commonly used Y. lipolytica Po1f strain. The engineered strain had a specific growth rate of 0.32 h−1 and a lipid content of 67.66 % (g/g DCW), which were 54 % and 26 % greater than those of the original strain. β-Carotene was used to verify the production of lipophilic natural compounds, and the highest yield was obtained 48 h earlier using the engineered strain compared to the original strain when consuming same carbon source. These findings show promise in using engineered Y. lipolytica for rapid growth and improved lipid utilization to boost efficiency of lipophilic product production.